Comparing therapeutic modulators of the SOD1 G93A Amyotrophic Lateral Sclerosis mouse pathophysiology - Lee, Albert J. B.; Kittel, Tyler E.; Kim, Renaid B.; Bach, Thao-Nguyen; Zhang, Tian; Mitchell, Cassie S. (Frontiers in Neuroscience, 2023)
Amyotrophic Lateral Sclerosis (ALS) is a paralyzing, multifactorial neurodegenerative disease with limited therapeutics and no known cure. The study goal was to determine which pathophysiological treatment targets appear most beneficial. A big data approach was used to analyze high copy SOD1 G93A experimental data. The secondary data set comprised 227 published studies and 4296 data points. Treatments were classified by pathophysiological target: apoptosis, axonal transport, cellular chemistry, energetics, neuron excitability, inflammation, oxidative stress, proteomics, or systemic function. Outcome assessment modalities included onset delay, health status (rotarod performance, body weight, grip strength), and survival duration. Pairwise statistical analysis (two-tailed t-test with Bonferroni correction) of normalized fold change (treatment/control) assessed significant differences in treatment efficacy. Cohen’s d quantified pathophysiological treatment category effect size compared to “all” (e.g. all pathophysiological treatment categories combined). Inflammation treatments were best at delaying onset (d=0.42, p>0.05). Oxidative stress treatments were significantly better for prolonging survival duration (d=0.18, p<0.05). Excitability treatments were significantly better for prolonging overall health status (d=0.22, p<0.05). However, the absolute best pathophysiological treatment category for prolonging health status varied with disease progression: oxidative stress was best for pre-onset health (d=0.18, p>0.05); excitability was best for prolonging function near onset (d=0.34, p<0.05); inflammation was best for prolonging post-onset function (d=0.24, p>0.05); and apoptosis was best for prolonging end-stage function (d=0.49, p>0.05). Finally, combination treatments simultaneously targeting multiple pathophysiological categories (e.g. polytherapy) performed significantly (p<0.05) better than monotherapies at end-stage. In summary, the most effective pathophysiological treatments change as function of assessment modality and disease progression. Shifting pathophysiological treatment category efficacy with disease progression supports the homeostatic instability theory of ALS disease progression.